Tradisi dan Modernitas Perspektif Seyyed Hossein Nasr - Encung, Encung (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article is intended to scrutinize Seyyed Hosssein Nasr?s thought about the negative dimensions of modernity and put it into the problems of the world where the idea of materialism ends due to greed of modern people. Nasr?s aim is actually to save humanity from destructive elements of modernity due to the idea of materialism, although the traditional-ism project that he proposed has still looked for a momentum within human consciousness and that is not to neglect the sacred matter in under-standing their world. In a reflection of his traditionalism, Nasr presupposes the creation of a progressive world presented with self-awareness to the existence of the Absolute and the Infallible. Nasr believes that modern people could live with their idea of perennial philosophy that connects everything in this world into the realm of the sacred. Benefits of modernity, according to Nasr, will be tarnished if people deny every sacred matter.